Edukasi Perawatan Mulut Pada Anak Sekolah Dasar Dengan Karies Gigi Di Wilayah Kerja Puskesmas Masohi - Riring, Jubaida; nuliana, wa (Jurnal Keperawatan Indonesia Timur (East Indonesian Nursing Journal), 2024)
Introduction: Dental caries is one of the dental disorders that often occurs in children due to the habit of consuming sweet foods/drinks and not maintaining dental hygiene. Dental caries can cause discomfort in daily life such as; activities, eating and drinking are disturbed, and reluctance to play. This condition, if not treated, will slow down the child's growth and development. One of the treatments that can be done is through dental and oral care education. Aims: To describe nursing care through dental and oral care education for elementary school children with dental caries in the Masohi Health Center Work Area. Method: This study is a descriptive study with a case study method, which was conducted for a week on 2 respondents with inclusion criteria of children aged 6-12 years with dental caries, willing to be respondents and cooperative during the study. Results: There was an increase in respondent knowledge after being given education on how to care for teeth and mouth, and both respondents were able to carry out dental and oral care by brushing their teeth properly and correctly. Suggestion: There needs to be supervision from parents to pay more attention to the time and how to brush children's teeth properly and correctly. Keywords: School children, Dental health, Oral care.